Comparison between two Real-time PCR assays and a nested-PCR for the detection of Toxoplasma gondii - Calderaro, A.; Piccolo, G.; Gorrini, et al., C. (Acta Biomedica Atenei Parmensis, 2006)
Background and aim of the work. In recent years, the diagnosis of toxoplasmosis has been improved by Real-time PCR assays. In this study we compared the performances of two Real-time PCRs (FRET and TaqMan protocols) already described in the literature, and one nested-PCR, currently used in our laboratory for the molecular diagnosis of toxoplasmosis. Methods. We evaluated the sensitivity and the specificity of a FRET- and a TaqMan-based Real-time PCRs targeting a 529 bp repeat region and the 18S RNA gene, respectively, and a nested-PCR, targeting the B1-gene of Toxoplasma gondii.We also tested, through nested-PCR, 46 biological samples obtained during a period of 29 months from pregnant women or immunocompromised patients with suspected T. gondii infection. Results. The analytical sensitivity of nested and TaqMan PCRs was approximately 103 tachyzoites/ml. FRET assay showed a sensitivity of 102 tachyzoites/ml. Three out of 46 biological samples were nested-PCR-positive and these results were also confirmed by both Realtime PCRs. Conclusions. Nested- and real-time PCRs evaluated in this study resulted very sensitive and specific; in particular FRET PCR resulted more sensitive than the other assays, probably because of the greater copy number of the target sequence. Real-time PCR assays are easy-to-use, producing results faster than conventional PCR systems and reducing contamination risks.